Metabolomic profile, anti-trypanosomal potential and molecular docking studies of Thunbergia grandifolia - Heba A. S. El-Nashar; Ahmed M. Sayed; Hany A. M. El-Sherief; Mostafa E. Rateb; Lina Akil; Ibrahim Khadra; Taghreed A. Majrashi; Sara T. Al-Rashood; Faizah A. Binjubair; Mahmoud A. El Hassab; Wagdy M. Eldehna; Usama Ramadan Abdelmohsen; et al. (Taylor & Francis Group, 2023)
Trypanosomiasis is a protozoan disease transmitted via Trypanosoma brucei. This study aimed to examine the metabolic profile and anti-trypanosomal effect of methanol extract of Thunbergia grandifolia leaves. The liquid chromatography-high resolution electrospray ionisation mass spectrometry (LC-HRESIMS) revealed the identification of fifteen compounds of iridoid, flavonoid, lignan, phenolic acid, and alkaloid classes. The extract displayed a promising inhibitory activity against T. brucei TC 221 with MIC value of 1.90 μg/mL within 72 h. A subsequent in silico analysis of the dereplicated compounds (i.e. inverse docking, molecular dynamic simulation, and absolute binding free energy) suggested both rhodesain and farnesyl diphosphate synthase as probable targets for two compounds among those dereplicated ones in the plant extract (i.e. diphyllin and avacennone B). The absorption, distribution, metabolism, excretion, and toxicity (ADMET) profiling of diphyllin and avacennone were calculated accordingly, where both compounds showed acceptable drug-like properties. This study highlighted the antiparasitic potential of T. grandifolia leaves.